Profile video construction as a means of institutional existence: ambon religious education and training center - Septri Rahayu (Balai Diklat Keagamaan Ambon, 2022)
This study aims to construct a video profile of the Ambon Religious Education and Training Center (BDK) which will be used as a medium to enhance the image and existence of the institution. This study uses the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages, namely concept, design, material collecting, assembly, testing, distribution. At the concept stage, goals and video outlines are determined, the design stage is by making a storyboard, the material collecting stage is by shooting and recording voice over according to the storyboard, the assembly stage is by editing all the assets that have been collected, the testing stage is by conducting video tests to leaders and partners, and the distribution stage by distributing videos via Youtube. All of these stages have succeeded in producing a multimedia product in the form of a video profile of BDK Ambon so that stakeholders and the general public can get information through video.